2017
DOI: 10.1186/s13058-016-0799-9
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive factors and the risk of triple-negative breast cancer in white women and African-American women: a pooled analysis

Abstract: BackgroundEarly age at menarche, nulliparity, late age at first completed pregnancy, and never having breastfed, are established breast cancer risk factors. However, among breast cancer subtypes, it remains unclear whether all of these are risk factors for triple-negative breast cancer (TNBC).MethodsWe evaluated the associations of these reproductive factors with TNBC, in 2658 patients with breast cancer (including 554 with TNBC) and 2448 controls aged 20–64 years, who participated in one of the three populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
59
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(86 citation statements)
references
References 78 publications
15
59
2
1
Order By: Relevance
“…Similarly, we observed that parity reduced the risk of luminal A and luminal B tumor subtypes in both young and older women. Our findings in BCYW were in accordance with previous case-control studies in young women (<45 years) [31,32]. However, we did not observe that this association differed significantly according to age (P > 0:05).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Similarly, we observed that parity reduced the risk of luminal A and luminal B tumor subtypes in both young and older women. Our findings in BCYW were in accordance with previous case-control studies in young women (<45 years) [31,32]. However, we did not observe that this association differed significantly according to age (P > 0:05).…”
Section: Discussionsupporting
confidence: 92%
“…BioMed Research International studies reported the opposite [32][33][34], as confirmed by our results. While parity has been confirmed to be related to a decreased risk of luminal BCYW, its relationship with TNBC remains uncertain.…”
supporting
confidence: 92%
“…14,20,21 Our finding of a 48% reduction in TNBC risk for younger parous women who breast-fed for 24 months is consistent with other studies [22][23][24][25] and a pooled analysis in African American and white women 26 that reported 40-50% risk reductions associated with breast-feeding for 12 months. Consistent with our results, the pooled analysis 26 and other studies 24,27-29 also failed Adjusted for base covariates, including age (continuous), study (AABCS, SFBCS and NC-BCFR), time period (1995-1999, 2000-2004 and 2005-2009) and race/ethnicity (African American, Asian American, Hispanic and non-Hispanic white). 2 Additionally adjusted for education (some high school or less, high school degree, vocational/technical school or some college and college or higher degree), family history of breast cancer in first-degree relatives (yes or no), height (quartiles) and oral contraceptive use (never, former and current).…”
Section: Discussionsupporting
confidence: 90%
“…For example, although overall rates of HR-negative/HER2-positive breast cancers in API women are similar to the rates in other groups, an analysis of California women by Asian ethnic subgroup reported that Korean, Filipina, Chinese, and Southeast Asian women had a higher risk of HR-negative/HER2-positive breast cancers compared with NHW women, whereas Japanese and American Indian women had lower risk for this subtype. 17 Racial and ethnic differences in breast cancer subtypes may reflect variation in the prevalence of breast cancer risk factors, particularly reproductive factors, which are most strongly associated with HR-positive breast cancers 15,18 but also appear to reflect ancestry-related genetic variations. [19][20][21] Stage distribution and survival Racial and ethnic variations in breast cancer stage at diagnosis and 5-year cause specific survival are shown in Figure 4.…”
Section: Cancer Occurrence In the Most Recent Time Periodmentioning
confidence: 99%